From Settlers to Subspecies: Genetic Differentiation in Commerson’s Dolphins Between South America and the Kerguelen Islands - Kraft, Sebastián; Pérez-Alvarez, MJosé; Olavarría, Carlos; Moraga, Rodrigo; Baker, C. Scott; Steel, Debbie; Tixier, Paul; Guinet, Christophe; Viricel, Amelia; Brickle, Paul; Costa, Marina; Crespo, Enrique; et al. (Frontiers in Marine Science, 2021)
Commerson’s dolphins (Cephalorhynchus commersonii) are separated into the subspecies C. c. commersonii, found along southern South America (SA) and the Falkland Islands/Islas Malvinas (FI/IM), and C. c. kerguelenensis, restricted to the subantarctic Kerguelen Islands (KI). Following the dispersal model proposed for the genus, the latter is thought to have originated from SA after a long-distance dispersal event. To evaluate this biogeographic scenario, a distribution-wide, balanced sampling of mitochondrial DNA (mtDNA) control region sequences was designed. New tissue samples from southern Chile, Argentina, FI/IM, and KI were added to published sequences from SA and KI, for a total of 256 samples. Genetic diversity indices, genetic and phylogeographic structure, and migration rates were calculated. One haplotype was shared between subspecies, with which all haplotypes of C. c. kerguelenensis formed a distinct group in the haplotype network. A new haplotype for C. c. kerguelenensis is reported. Differentiation in haplotype frequencies was found among localities within the distribution of C. c. commersonii, yet the phylogeographic signal was only statistically significant between subspecies. Coalescent-based historical gene flow estimations indicated migration between the northern and southern portions of the species’ range in SA as well as between SA and the FI/IM, but not between these and the KI. The net nucleotide divergence between dolphins from SA and the FI/IM was lower than the recommended threshold value suggested for delimiting subspecies, unlike that found between C. c. commersonii and C. c. kerguelenensis. The results are consistent with the model of post-glacial colonization of KI by South American C. commersonii, followed by an ongoing divergence process and subspecies status. Thus, C. c. kerguelenensis may represent the most recent diversification step of Cephalorhynchus, where isolation from their source population is driving a process of incipient speciation.